The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.15421/022317
|View full text |Cite
|
Sign up to set email alerts
|

The influence of feeding level on the growth of pigs depending on their genotype

Abstract: The growth and development of pigs is determined by their genotype and environmental conditions (primarily the level of feeding), however, the number of works aimed at studying the complex influence of genetic and non-genetic factors in their interaction is currently insufficient. The purpose of our work was to estimate the effect of the MC4R genotype, feeding level and interaction of these factors on growth and backfat thickness of crossbred pigs and to investigate the possibility of correcting the melanocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…This causes poor animal welfare in addition to being an economic issue for the pig business (Muro et al, 2022). Since previous studies (Vashchenko et al, 2023) found that the MC4R genotype, under the condition of a high level of feeding, leads to an increase in the thickness of the backfat in pigs by 8.1-11.3%, therefore, in this work, the emphasis was placed on finding the effect of this marker on reproductive ability.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This causes poor animal welfare in addition to being an economic issue for the pig business (Muro et al, 2022). Since previous studies (Vashchenko et al, 2023) found that the MC4R genotype, under the condition of a high level of feeding, leads to an increase in the thickness of the backfat in pigs by 8.1-11.3%, therefore, in this work, the emphasis was placed on finding the effect of this marker on reproductive ability.…”
Section: Discussionmentioning
confidence: 98%
“…Genotypes that contribute to better performance under the same conditions can have a negative effect when the feeding conditions are changed. For example, pigs with the MC4R AG genotype had better live weight compared to MC4R GG genotype carriers when fed a diet high in energy, protein and essential amino acids, but performed significantly worse under restricted feed conditions (Vashchenko et al, 2023). In other studies, pigs with the same genotype (MC4R AA) had the best average daily gains when fed ad libitum, and the worst gains and feed conversion when fed a restricted diet (Calta et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Відставання на початкових етапах розвитку, може бути лише в деякій мірі вирівняне за рахунок компенсаторного росту, проте досягти повноцінного заміщення втрачених приростів практично неможливо [5][6][7][8]. Ріст і розвиток молодняку свиней, також як і відтворювальна продуктивність основного поголів'я залежить від генетичних і паратипових факторів [9][10][11].…”
Section: вступunclassified
“…The frequency of the A allele at the locus (SNP c.1426 G>A) in the population of 2018 was 0.750, which distinguished the Myrhorod breed from modern breeds, in which the G allele usually predominates (Vashchenko et al, 2019). SNP marker MC4R c.1426 G>A, according to the data of a significant number of studies (Davoli et al, 2012;Calta et al, 2022;Vashchenko et al, 2023), related to lard thickness and intensity of feed consumption in pigs. Such an effect is due to the fact that the mutation in this locus disrupts normal G protein coupling in the MC4R signaling to adenylyl cyclase (Ovilo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%